FACTORS AFFECTING REVENUE LEVEL OF RUBBER FARMERS (Case Study at Musi Banyuasin, South Sumatra, Indonesia) - Iman Satra Nugraha (Agricultural Socio-Economics Journal, 2019)
Musi Banyuasin is a district which has the potential of rubber plantations, oil and gas companies. Corporate responsibility is one of them is to develop the area around the company's operations. This study aims to determine the factors that affecting the income of farmers program and non-program in the area of company operations. Respondents were chosen purposively to the rubber farmers who divided in two categories, in this case 50 respondents by program and non-program. Data collection used interview method with questionnaire. Data were analyzed quantitatively. The results showed that all variables significantly affect to the farmers' income at a real level of 12%. It is seen significance value 0.000 < α 12%. The variables that affect the farmer's income of the program (X2), The farmers' rubber program price (X4), the total production farmers program (X6), and the amount of non-program farmer's rubber production (X7). Total Revenue farmers program IDR 3,700,000 per month and rubber farming activities contribute to revenue as much as IDR 2,800,000. While the total revenue from non-program farmers is equal IDR 2,779,000 per month and rubber farming activities contribute to revenue as much as IDR 1,820,000 per month.